Transformation Prospect of a Non Disaster-Prepared-School in Implementing Management of Child Safety Education (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2020)
Primary School X is an inclusive primary school that enrolls children with special needs, located in a disaster-prone area and never been exposed to information and training related to child safety education. The purpose of this study is to investigate the readiness of Primary School X as a non disaster-prepared inclusive-primary-school in implementing child safety education management. This study combined descriptive and analytic studies. Descriptive study was used to assess school management condition through 28 assessment and was conducted through interviews, document study and observation. The analytic study used was quasi-experimental study with one group pre- and post-test design. The result showed that the readiness level of Primary School X to transform into multi-disaster-based child safety was 36%, which is included into transformation â€œreadyâ€ category.